The viral infections disease in discrete epidemic model with treatment - Lafta, Alaa Hussein (Iraqi Journal of Science, 2026)
In this research, the viral infections disease in discrete epidemic model with treatment is presented. The treatment function imposed inside SIV model to see their effects. The conditions for the positivity of solutions to endemic and epidemic points are found and also conditions that require to achieve local stability of all the equilibria are satisfied. Possibility of bifurcation and chaos are discussed. Furthermore, the numerical analysis validates the established theoretical results by using MATLAB program and the iterative method was employed. Also, the influence of the treatment on the model’s behavior confirmed numerically.